Transformations of Publicism in the New Media and Digital Communication Environment - Abrahamyan, Gor (Bulletin of Yerevan University B: Philology, 2025)
The article explores the transformations of journalism as a unique form of creative activity in the context of new media and digital communication, against the background of the historical functional role of traditional media practice. It argues that the technological advancements of new media have fundamentally altered the forms and methods of communication, impacting the mechanisms of shaping public discourse and influencing public opinion. The article analyzes how social media and digital technologies affect the social and public role of journalism, focusing on phenomena such as the dehumanization of media, audience segmentation, content fragmentation, and the crisis of authority in the digital communication environment. It discusses both the opportunities provided by new media for modernizing journalism and the challenges encountered along this path, offering solutions to preserve the ethical and value-based content and meaning of journalism in the digital environment